Peran Umar Bin Khattab dalam Manajemen Konflik - Yuana Tri Utomo (At-Tauzi : Jurnal Ekonomi Islam, 2017)
Omar ibn Khattab's era revealed good management from all sides of life. In performing his duties, Omar faced conflict because conflict always happens in life. Along with the development of Islamic Daulah, the problems faced by Muslims increasingly complex. Omar as a leader must be able to manage the various problems in order to take care of the needs of the Muslims. This study aims to determine the role of Omar ibn Khattab in managing the conflicts that occurred during his leadership. This research is included in qualitative-descriptive research with historical method so that data is obtained through books that discuss the life history of Omar ibn Khattab. The data analysis techniques using interactive models and triangulation of sources to obtain valid and reliable data. The results of this study indicate that the conflict in Omar's era occurred at the beginning and end of leadership. In conflict management, Omar ibn Khattab uses different methods of settlement depending on the problems at hand. Omar tends to use settlement methods with integrative problem solving and domination. Omar ibn Khattab's leadership directed the conflict to be resolved completely by applying the rules as appropriate